The influence of service quality and product innovation on customer satisfaction at bank mandiri taspen - Istiqlal, Istiqlal; Hadi, Sulhan (Jurnal Mantik, 2024)
This study aims to analyze the effect of product innovation and service quality on customer satisfaction at Bank Mandiri Taspen. A quantitative approach with simple random sampling method was used to collect data from 91 customers in Mataram City, NTB. Data were obtained through an online questionnaire with a Likert scale and analyzed using multiple linear regression through SPSS. The validity test with Pearson correlation indicated a very strong and significant relationship between service quality, product innovation, and customer satisfaction, with a correlation value above 0.98 at the 99% significance level. In addition, the reliability test using Cronbach's Alpha gave a value of 0.997, which indicates that the measurement instrument has a very high level of internal consistency. The results showed that product innovation and service quality had a significant effect on customer satisfaction, with unstandardized coefficients of 1.332 and -0.351, respectively. The R Square value of 0.990 indicates that these two variables explain 99% of the variation in customer satisfaction. This research is in line with previous studies that emphasize the importance of product innovation in improving customer satisfaction. Bank Mandiri Taspen is advised to continue to innovate their products and improve aspects of service quality that may be less satisfying for customers. Future research is recommended to explore other factors such as customer trust and user experience in the context of digital banking